Constructing of 3D novel chaotic hidden attractor and circuit implementation - Mohamad Afendee, Mohamed; Aceng, Sambas; Sundarapandian, Vaidyanathan; Mustafa, Mamat; Mada Sanjaya, W.S. (International Science Press, 2017)
A 3D novel chaotic hidden attractor with no equilbrium is investigated in this paper. Some dynamical properties and behaviors of this system are described in terms Lyapunov exponents, time series and phase portraits. Furthermore, An electronic circuit realization of the 3D novel chaotic hidden attractor is presented in details. Finally, the circuit experimental results of the 3D novel chaotic hidden attractor show agreement with the numerical simulations.